Creating a Phase Change Thermal Energy Measurement System (Part 1: Design and Construction). - Ulrich, Daniel C.; Thrift, Ben C.; Siahpush, Ali (Journal of the Utah Academy of Sciences, Arts & Letters, 2018)
In the last 40 years, interest has grown significantly in the utilization of passive thermal energy stored or released during the phase change of a substance. A variety of applications exist for the use of latent heat energy such as building heating, ventilation, and air conditioning systems, electronics cooling, and passive heating and cooling of instruments in space. Studies have been conducted in this field, but there are still many possibilities for undergraduate engineering research to lead to new advancements in the field of phase change heat transfer. The objective of this project was to design and construct a test-system to be utilized for undergraduate experimentation and research in the thermal behavior of the solid-liquid phase change materials. The system consisted of a vertical copper test cylinder (vessel) that was heated and cooled inwardly by using copper tubing wrapped in a counterflow arrangement around the outside of the test vessel. The copper tubing is connected to a constant temperature bath (CTB) that can provide fluid to heat or cool the copper vessel in the range of -20°C to 100°C. The progress of the phase change was monitored using an array of more than 100 thermocouples. Currently, water is being utilized as the phase change material to validate the test system. Future work will consist of testing 99% pure eicosane (CH), investigating the use of porous copper foam in conjunction with eicosane to improve heat transfer performance, and measurement of the thermal conductivity of the porous media saturated with the phase change material. Future users of the test system will be able to gain a better understanding of how this phase change energy is stored and released in different materials and applications.